ASA Classification Pre-Endoscopic Procedures: A Retrospective Analysis on the Accuracy of Gastroenterologists. Issue 2 (February 2017) - Theivanayagam, Shoba; Lopez, Kristi T.; Matteson-Kome, Michelle L.; Bechtold, Matthew L.; Asombang, Akwi W.
Abstract : Objectives: Before an endoscopic procedure, an evaluation to assess the risk of sedation is performed by the gastroenterologist. To risk stratify based on medical problems, the American Society of Anesthesiologists (ASA) classification scores are used routinely in the preprocedure evaluation. The objective of our study was to evaluate among physicians the ASA score accuracy pre-endoscopic procedures. Methods: At a single tertiary-care center an institutional review board–approved retrospective study was performed. Upper endoscopies performed from May 2012 through August 2013 were reviewed; data were collected and recorded. Statistical analysis was performed using descriptive statistics and linear weighted kappa analysis for agreement (⩽0.20 is poor agreement, 0.21–0.40 is fair, 0.41–0.60 is moderate, 0.61–0.80 is good, and 0.81–1.00 is very good). Results: The mean ASA scores by the gastroenterologist compared with the anesthesiologist were 2.28 ± 0.56 and 2.78 ± 0.60, respectively, with only fair agreement (weighted kappa index 0.223, 95% confidence interval [CI] 0.113–0.333; 48% agreement). The mean ASA scores for gastroenterologists compared with other gastroenterologists were 2.26 ± 0.5 and 2.26 ± 0.44, respectively, with poor agreement (weighted kappa index 0.200, 95% CI 0.108–0.389; 68% agreement). Agreement on ASA scores was only moderate between the gastroenterologist and himself or herself (weighted kappa index 0.464, 95% CI 0.183–0.745; 75% agreement). Conclusions: Gastroenterologists performing preprocedure assessments of ASA scores have fair agreement with anesthesiologists, poor agreement with other gastroenterologists, and only moderate agreement with themselves. Given this level of inaccuracy, it appears that the ASA score pre-endoscopy is of limited significance. Abstract : This was a single-center retrospective study examining American Society of Anesthesiologists (ASA) score accuracy among physicians in advance of endoscopic procedures. The authors not only analyzed gastroenterologists compared with anesthesiologists but also examined individual performances and performance among gastroenterologists. The study showed that gastroenterologists performing preprocedure assessment of ASA scores have fair agreement with anesthesiologists, poor agreement with other gastroenterologists, and only moderate agreement with selves. Given this level of inaccuracy, it appears that the ASA score pre-endoscopy is of limited significance.